Decentralization, agricultural services and determinants of input use in Nigeria - Akramov, Kamiljon T. (International Food Policy Research Institute, 2010)
The substantial differences in agricultural productivity between Asia and Africa can be largely explained by differences in use of modern inputs. The evidence suggests that better access to infrastructure (such as roads and irrigation) and agricultural services has given Asian farmers significantly better access to modern inputs, while Sub-Saharan African farmers without such an access are not able to fully exploit the benefits of modern agricultural inputs. This brief discusses the relationship between agricultural service provision and modern input use by farmers in Nigeria, with a focus on the differences among states and local government areas (LGA).